BATASAN DAN MEKANISME PENERAPAN SANKSI PIDANA PERPAJAKAN DI INDONESIA DALAM PERSPEKTIF ASAS ULTIMUM REMEDIUM - Safitri, Eka Ayu; Damayanti, Ratih; Sulistiyono, Tri (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study examines the limitations and mechanisms of the application of criminal sanctions against taxpayers who violate tax provisions in Indonesia, and evaluates the application of the ultimum remedium principle as the principle of